Evaluation of selected physico-chemical, colour and textural characteristics of market Gulabjamun - Sukre, Vivekanand Natha; Barnwal, Pradyuman; Chavhan, Bhavesh B; Deep, Ankit; Bhagat, Pooja N (Indian Journal of Dairy Science, 2021)
Gulabjamun is one of the most popular traditional Indian dairy products. The various characteristics such as physico-chemical, colour and textural quality characteristics of six brands of Gulabjamun were investigated which plays important role in its marketing and consumer acceptance. The fat and unit-weight of market Gulabjamun were found statistically highly significantly different (p